The Development of Teaching Material of Competency-Based- Ilmu Badi’ in The Study Program of Arabic Language Education, FBS UNM - Fatkhul Ulum; Susiawati Susiawati; Fauziah Bachtiar (Seminar Nasional LP2M UNM, 2021)
Summary. This was a descriptive research aimed at developing a teaching material of competency-based-ilmu badi’ as one of alternative ways in improving education quality, particularly, in terms of the teaching of ilmu badi’ in the study program of Arabic language education, FBS UNM. The research type was research and development (R & D) following the 4-D developmental model of Thiagarajan. The research population was all students of the study program of Arabic language education, FBS UNM, consisting of 7 classes. Meanwhile, the research sample was one class of the students in the sixth semester that were taking the Balaghah 2 or Ilmu badi’ course. The instruments utilized in this research were a validation sheet of the teaching material, learning achievement test, questionnaire for students’ responses, and researchers’ field note. This research results in a product such a teaching material of Ilmu badi’ based on competency approach. Building on the validation result to the teaching material and the test result, it is acquired from the content expert that the teaching material is in the validity level as 88,33% and from the pedagogical expert that it is in the validity level as 90,66%. Whereas, the try out results show that the teaching material is practical with the score of 79,74% and it is highly effective with the average of the students’ score as 83,54. It means that the developed teaching material is effective, valid, and practical to use.Keywords: Development of Teaching Material, Ilmu Badi’, Competency